The Phenomenon of Startup Investment and Minority Investor Protection: A Legal Analysis of Asymmetric Risk - polontoh, Herry m; Yusnita, Yusnita; Judijanto, Loso; Suhermi, Suhermi (PT. Anagata Sembagi Education, 2025)
The rapid growth of the startup industry in Indonesia has raised new legal issues related to the protection of minority investors in a dynamic and institutionally unestablished ownership structure. This study analyzes how the risk of information asymmetry in the relationship between founders and investors creates inequality in legal relations that weakens the position of minority investors. Through a normative juridical approach, this study examines the effectiveness of the provisions in Law Number 40 of 2007 concerning Limited Liability Companies, especially Articles 61, 62, and 114, in providing substantive legal protection. The results of the study show that the existing legal mechanism is not fully adaptive to the complexity of the startup investment model, especially due to the weak application of fiduciary duty principles and the lack of application of good corporate governance principles. On the other hand, the practice of investment agreements often affirms the dominance of the majority shareholders through exploitative clauses. Therefore, a legal reformulation is needed that is able to bridge this normative vacuum, through the strengthening of hybrid legal instruments and responsive sectoral regulations. This research recommends legal policy reforms that emphasize the balance of interests, transparency, and substantive justice to create an inclusive, sustainable, and economically democratic startup ecosystem.